2006
DOI: 10.1111/j.1349-7006.2006.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic polymorphisms of MDR1, FMO3 and CYP1A2 on susceptibility to colorectal cancer in Koreans

Abstract: The aim of the present study was to evaluate the effects on the susceptibility to colorectal cancer (CRC) of genetic polymorphisms in P-glycoprotein (PGP) and the metabolic enzymes cytochrome P450 1A2 (CYP1A2) and flavin-containing monooxygenase 3 (FMO3). We analyzed five single-nucleotide polymorphisms (SNP) in 93 cancer-free volunteers and 111 patients with CRC: one common genetic variant of the PGP-encoding MDR1 gene and four SNP in genes for metabolic enzymes (two SNP in FMO3 and two SNP in CYP1A2). The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 33 publications
2
38
2
Order By: Relevance
“…In agreement with our results, Andersen and co-workers found that carriers of C allele of the C3435T polymorphism had an increased risk of CRC in Norwegian Caucasian population (Andersen et al, 2009). On the contrary, in an Iran population investigation, T allele of the ABCB1 C3435T polymorphism showed significantly increased risk of CRC (Khedri et al, 2011), while others did not find any statistically significant associations (Bae et al, 2006;Samanian et al, 2011). Regarding ABCB1 G2677T/A genotypes and risk for CRC, we did not find any correlation between CRC risk and the investigated G2677T/A genotypes, likewise, De Iudicibus et al found no relation between ABCB1 G2677T/A polymorphism and CRC patients (De Iudicibus et al, 2008).These data suggest that the role of the ABCB1 polymorphisms in cancer risk may vary with ethnicity, a possibility that warrants further investigation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In agreement with our results, Andersen and co-workers found that carriers of C allele of the C3435T polymorphism had an increased risk of CRC in Norwegian Caucasian population (Andersen et al, 2009). On the contrary, in an Iran population investigation, T allele of the ABCB1 C3435T polymorphism showed significantly increased risk of CRC (Khedri et al, 2011), while others did not find any statistically significant associations (Bae et al, 2006;Samanian et al, 2011). Regarding ABCB1 G2677T/A genotypes and risk for CRC, we did not find any correlation between CRC risk and the investigated G2677T/A genotypes, likewise, De Iudicibus et al found no relation between ABCB1 G2677T/A polymorphism and CRC patients (De Iudicibus et al, 2008).These data suggest that the role of the ABCB1 polymorphisms in cancer risk may vary with ethnicity, a possibility that warrants further investigation.…”
Section: Discussionsupporting
confidence: 78%
“…However, Andersen et al reported that carriers of the variant allele of MDR1 C3435T had a lower risk of CRC than homozygous C allele carriers (Andersen et al, 2009). Moreover, Bae et al found no association of the ABCB1 C3435T polymorphism with CRCs in Koreans (Bae et al, 2006). In addition, the G2677T polymorphism was reported to be significantly associated with CRCs with high microsatellite instability (Samanian et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, certain FMO3 polymorphisms are not associated with common diseases such as colorectal cancer and hypertension [68,69]. This is one gray area illustrative of the amount of additional research needed to establish the significance of FMO3 polymorphisms in human diseases and their management.…”
Section: Resultsmentioning
confidence: 99%
“…CYP1A1*2A, CYP1A1*2B and CYP1A1*4 polymorphisms have been found that might be associated with cancers of lung, esophagus or breast and with acute myeloid leukemia [54][55][56][57], while the CYP1A2*1F polymorphism might be associated with an increased risk of colorectal cancer [52]. In addition, the CYP1A2*1C allele has been associated with decreased caffeine 3-demethylation [58], and the CYP1A2*1F allele was correlated to increased activity [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the CYP1A1 and CYP1A2 genes are polymorphic [39,49,52,53]. CYP1A1*2A, CYP1A1*2B and CYP1A1*4 polymorphisms have been found that might be associated with cancers of lung, esophagus or breast and with acute myeloid leukemia [54][55][56][57], while the CYP1A2*1F polymorphism might be associated with an increased risk of colorectal cancer [52].…”
Section: Discussionmentioning
confidence: 99%